Paradoks literasi matematika: analisis kegagalan implementasi langkah polya pada masalah berstandar TIMSS - -, Sutra; Majid, Ahmad Farham; Shadiq, Muh Ibnu; Ramadhani, Nurul Aulia (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Purpose: This study dissects TIMSS-based mathematical literacy difficulties in Relation and Function topics using Polya’s framework to bridge the gap between global standards and students' cognitive realities. Design/methodology/approach: Employing a descriptive qualitative design, data were gathered from 21 tenth-grade students through problem-solving tests and in-depth interviews, then analyzed to map difficulty profiles across varying ability levels. Findings: Results reveal stratified obstacles: high-ability students struggle with accuracy; middle-ability with strategic maturity; while low-ability students face systemic failure across all Polya stages due to weak fundamental concepts and poor time management. This confirms that literacy barriers are rooted in metacognitive failures during solution evaluation. Practical implications: These findings advocate for differentiated learning and systematic heuristic training to accommodate diverse cognitive profiles in meeting international assessment standards. Originality/value: This study offers a specific diagnostic on Relation and Function topics within a madrasah context, enriching the literature on mapping mathematical literacy barriers contextualized against global TIMSS indicators. Purpose: Penelitian ini membedah kesulitan literasi matematika berstandar TIMSS pada materi Relasi dan Fungsi menggunakan kerangka Polya guna menjembatani celah antara standar global dan realitas kognitif peserta didik. Design/methodology/approach: Melalui desain deskriptif kualitatif, data dikumpulkan dari 21 siswa kelas X melalui tes pemecahan masalah dan wawancara mendalam, lalu dianalisis secara sistematis untuk memetakan profil kesulitan berdasarkan tingkat kemampuan.Findings: Temuan menunjukkan stratifikasi hambatan: siswa berkemampuan tinggi terkendala akurasi; kategori sedang terhambat pada maturitas strategi; sementara kategori rendah mengalami kegagalan sistemik di seluruh tahap Polya akibat lemahnya konsep fundamental dan manajemen waktu. Ini mengonfirmasi bahwa kesulitan literasi berakar pada hambatan metakognitif dalam mengevaluasi solusi. Practical implications: Hasil ini merekomendasikan implementasi pembelajaran berdiferensiasi (differentiated learning) dan penguatan prosedur heuristik untuk mengakomodasi keberagaman profil kognitif siswa dalam menghadapi penilaian internasional. Originality/value: Studi ini memberikan diagnosa spesifik pada materi Relasi dan Fungsi dalam konteks madrasah, memperkaya literatur pemetaan hambatan literasi matematika yang dikontekstualisasikan langsung dengan indikator global TIMSS.